2022
DOI: 10.3389/feart.2022.840250
|View full text |Cite
|
Sign up to set email alerts
|

Actionable Information in Flood Risk Communications and the Potential for New Web-Based Tools for Long-Term Planning for Individuals and Community

Abstract: Because of its ubiquitous nature and catastrophic impacts, flood information should be readily available and continually evaluated, to maximize utility for the public and professionals. Web-based tools can fill existing needs for actionable information to inform decisions regarding flood damage mitigation for new and existing structures. The goal of this research is to identify the current capabilities, gaps, and future demands of Web-based flood communication systems. To understand the current and potential n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 123 publications
(107 reference statements)
1
29
0
Order By: Relevance
“…The first Intergovernmental Panel on Climate Change (IPCC) report (Cutter et al, 2012) confirmed these assertions by reporting that societal exposure (and therefore risk as defined here) is a product of development processes on hazardous landscapes and also is an anticipated key driving force contributing to future vulnerability to extreme weather events (Pielke Sr et al, 2007;Hinkel et al, 2010). There remains a paucity of risk assessment work at a scale more local than countylevel, especially while also considering changing hazard intensities (Gnan et al, 2022a(Gnan et al, , 2022bMostafiz et al, 2022b, Mostafiz et al, 2022Rahim et al, 2022).…”
Section: Introductionmentioning
confidence: 81%
“…The first Intergovernmental Panel on Climate Change (IPCC) report (Cutter et al, 2012) confirmed these assertions by reporting that societal exposure (and therefore risk as defined here) is a product of development processes on hazardous landscapes and also is an anticipated key driving force contributing to future vulnerability to extreme weather events (Pielke Sr et al, 2007;Hinkel et al, 2010). There remains a paucity of risk assessment work at a scale more local than countylevel, especially while also considering changing hazard intensities (Gnan et al, 2022a(Gnan et al, , 2022bMostafiz et al, 2022b, Mostafiz et al, 2022Rahim et al, 2022).…”
Section: Introductionmentioning
confidence: 81%
“…With no comprehensive flood risk assessment that quantifies flood losses and provides actionable information (Mostafiz et al, 2022c), landlords and tenants are unlikely to be aware of flood risk to which they are exposed and the possible benefits from mitigation measures. Being aware of the full flood risk, mitigation options, and economic implications enhances investment and occupation decisions.…”
Section: Discussionmentioning
confidence: 99%
“…We draw on Zade et al (2018), to define and delineate actionable information, which they define as information on which decision-makers need to respond and decide. In our work we especially apply short-term actionable information as defined by Mostafiz et al (2022), because we address the issue of immediate response with flood hazards. Mostafiz et al (2022) understand long-term actionable information as information that can help coping with hazards in the preparation or recovery phase.…”
Section: Actionable Information For Decisionmakersmentioning
confidence: 99%
“…In our work we especially apply short-term actionable information as defined by Mostafiz et al (2022), because we address the issue of immediate response with flood hazards. Mostafiz et al (2022) understand long-term actionable information as information that can help coping with hazards in the preparation or recovery phase. Especially concerning short-term actionable information, producing the right information to the right decision-makers at the right time helps members of an EOC overcome multiple challenges such as limited resources in SMA, and information overload in a timeand safety-critical work environment.…”
Section: Actionable Information For Decisionmakersmentioning
confidence: 99%
See 1 more Smart Citation